ANTI-FUNGAL ACTIVITY OF ESSENTIAL OIL DISTILLED FROM ETHANOL EXTRACT OF Piper betle L. LEAVES COLLECTED FROM SEVERAL REGION IN YOGYAKARTA, AGAINTS Candida albicans - Triana Hertiani; Indah Purwantini (Indonesian Journal of Pharmacy, 2002)
Anti-fungal activity of essential oil distilled from exctracts of Piper betle leaves against Candida albicans and the gas chromatography profiles has been studied. The leaves were collected from Kaliurang, Kulonprogo, and Gunung Kidul. This research was aimed to find out the influences of extract production process and the difference of starting material source regions to anti-fungi activities against Candida albicans. The gas chromatographic profile of essential oils distilled from sirih (Piper betle L.) extracts were also observed. The essential oils used in this research was collected from ethanol 95% extract of sirih dried leaves by distillation method. Anti-fungi activity was assayed using Sabaroud agar-diffusion method. The results showed that the essential oil from Kulonprogo has the highest activity. The gas chromatographic profile of each essential oil had been examined individually and the results showed that the composition of substances containing in each extracts were different. The study comparison of essential oils composition of Piper betle L. fresh herbs showed that the extraction method reduced the anti-candida potency of Piper betle L. leaves extract. The habitat of the starting materials influences the gas chromatographic profile of the essential oil.Key words: Piper betle Leaves Extract; anti-fungi, chromatographic profiles